The role of avoidance‐based coping in the psychosocial functioning of weight loss treatment‐seeking adults. (9th September 2015) - Lillis, J.; Wing, R. R.
Summary Objective The aim of this study was to determine the role of avoidance‐based coping in the psychosocial functioning of weight loss treatment‐seeking persons with obesity who report high internal disinhibition. Methods Participants were 162 overweight or obese adults entering a behavioural weight loss intervention programme who reported high internal disinhibition at screening. We conducted multivariate regression analyses by using mental and physical quality of life and satisfaction with relationships as dependent variables and examining the association of demographic variables, experiential avoidance (avoidance‐based coping) and symptoms of depression. We hypothesized that higher levels of experiential avoidance and symptoms of depression would be associated with poorer mental and physical quality of life and relationship satisfaction. Post‐hoc analyses examined results relative to non‐obese norms. Results Both experiential avoidance and depression were significantly and independently associated with each of the three psychosocial outcome measures. Individuals who were high on both experiential avoidance and depression scored significantly below the population mean for non‐clinical samples on mental and physical quality of life and relationship satisfaction. Conclusion In a sample of weight loss treatment‐seeking adults with high internal disinhibition, elevated levels of experiential avoidance and psychological symptoms are prevalent. Adding intervention components specifically designed to address unhealthy coping could results in improvements in overall psychosocial functioning and possibly weight loss.